2021
DOI: 10.1155/2021/9071057
|View full text |Cite
|
Sign up to set email alerts
|

Reticulocyte Hemoglobin Equivalent: Diagnostic Performance in Assessment of Iron Deficiency in Patients with Hypothyroidism

Abstract: Introduction. Iron deficiency affects approximately 30% of the world population and is frequently encountered in hypothyroid patients. Early recognition and prompt treatment of iron deficiency in hypothyroid patients lead to a favorable outcome. The aim of this study is to prove the usefulness of reticulocyte hemoglobin equivalent (Ret-He) as a reliable and effective tool in diagnosis of iron deficiency in hypothyroid patients. Materials and Methods. 154 patients with hypothyroidism were included in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…While iron was an essential trace element for the human body, parameters related to iron metabolism were not specific for IDA. The diagnosis challenges of IDA raised since standard biomarkers might be altered in a complex patient population with conditions such as cancer [ 13 ], inflammatory diseases like Inflammatory Bowel Disease (IBD) [ 14 ], or other chronic diseases [ 9 , 15 , 16 ]. Our study explored whether MCHr was a potential alternative rapid indicator for the diagnosis and monitoring of IDA [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…While iron was an essential trace element for the human body, parameters related to iron metabolism were not specific for IDA. The diagnosis challenges of IDA raised since standard biomarkers might be altered in a complex patient population with conditions such as cancer [ 13 ], inflammatory diseases like Inflammatory Bowel Disease (IBD) [ 14 ], or other chronic diseases [ 9 , 15 , 16 ]. Our study explored whether MCHr was a potential alternative rapid indicator for the diagnosis and monitoring of IDA [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…in ammatory diseases such as IBD [14], or other chronic diseases [9,15,16]. It is reported that MCHr was an attractive alternative rapid indicator for the diagnosis and monitor of IDA [13].…”
Section: Discussionmentioning
confidence: 99%
“…Transferrin saturation was obtained by using formula serum iron  total iron binding capacity  100. A cutoff of 30.8 pg for Ret-He was taken as it had specificity and sensitivity of 90% for detecting iron deficiency coexisting with anemia of chronic disorder according to a study by Wardah A et al [8].…”
Section: Methodsmentioning
confidence: 99%